The need to know: The information needs of parents of infants with an intellectual disability—a qualitative study. (15th May 2017) - Douglas, Tracy; Redley, Bernice; Ottmann, Goetz
Abstract: Aim: The aim of this study was to explore the information needs of parents of infants with an intellectual disability in the first year of life. Background: Parents whose infant has an intellectual disability need access to information if they are to facilitate optimal care for their child. A lack of timely, accurate information provision by health professionals, particularly nurses and midwives, can increase parental stress and hinder access to the supports they and their infant require. Design: A qualitative descriptive methodology was used for the study. Methods: Qualitative interviews were undertaken with parents of 11 children with intellectual disabilities in Victoria, Australia in 2014. Data were analysed using descriptive thematic analysis. Findings: Parents experienced challenges accessing quality information during the first year of their child's life. Parents required incremental information provision to build a strong knowledge base to facilitate optimal care for their infants. Three types of knowledge were identified as crucial for parents: knowledge about (1) the infant's condition; (2) the infant's specific needs and (3) available supports and services. Health professionals were the key resource to access this information. Conclusion: Health professionals' responsibilities include providing relevant, timely information to parents of infants with intellectual disabilities. This study conceptualises three types of information parents need to develop a strong knowledge base to guide their infant's care and provides guidance concerning the optimal timing for the delivery of information.